An equivalence result for (Logit) QRE and Level-k - Morales-Siles, Antonio José (My University, 2016)
The logit QRE has comparative statics properties that are in some cases more intuitive than for the standard NE, and it explains experimental data that are consistent with intuition but are not predicted by the Nash equilibrium. In this paper we show that level-k model reproduces the same comparative statics and offers predictions close to the logit QRE within the class of (symmetric) games with the local payoff property.
Keywords: Juegos, Teoría de; Bounded rationality; Quantal response; Local payoff property